Usefulness of Electromyography to Predict Future Muscle Weakness in Clinically Unaffected Muscles of Polio Survivors. Issue 7 (16th January 2020) - Sawada, Koshiro; Horii, Motoyuki; Imoto, Daisuke; Ozaki, Kenichi; Toyama, Shogo; Saitoh, Eiichi; Mikami, Yasuo; Kubo, Toshikazu
Abstract : Background: Post‐polio syndrome–induced muscle weakness may develop in limbs that have had normal muscle strength and have been considered unaffected by polio. Objective: To investigate the utility of electromyography (EMG) for predicting future muscle weakness in clinically unaffected limb muscles of polio survivors. Design: Retrospective study. Setting: Academic polio clinic. Participants: Polio survivors (N = 77) who underwent EMG between April 2008 and March 2010 and were followed for at least 2 years. Materials and Methods: Chart reviews were conducted to extract baseline EMG and manual muscle strength test (MMT) results to investigate the relationship between baseline EMG abnormalities and change in muscle strength over 2 years for various upper and lower limb muscles that control movement in the limb joints. Main Outcome Measurements: Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of EMG findings for prediction of subsequent muscle weakness. Results: EMG data were available for 44 deltoid, 59 biceps brachii, 60 triceps brachii, 59 vastus lateralis, 59 tibialis anterior, and 55 gastrocnemius (medial head) muscles. The percentage of muscles with an initial MMT of grade 5 that developed weakness over 2 years of follow‐up was approximately 15% for most muscle types. Sensitivity of EMG to predict subsequent weakness was higher in the lower limbs (0.67‐1.00). Specificity was higher in the biceps brachii (0.83). PPV was higher in the biceps brachii (0.50). NPV was higher in the lower limbs (0.89‐1.00) but lower in the deltoid (0.75). Conclusion: EMG abnormalities were detected in some clinically normal muscles of polio survivors. EMG abnormalities predicted muscle weakness 2 years later, although the strength of this relationship varied depending on the muscle.